Socioeconomic analysis of the small cocoa producers of the el Guabito compound, Mocache Canton, Los Ríos Province, Ecuador (Teorías, Enfoques y Aplicaciones en las Ciencias Sociales, 2020)
Agriculture is, after oil, the second economic activity in the primary sector that generates the most resources in Ecuador because it has an economy characterized by decades as a primary exporter. Regarding cocoa, Ecuador is the country with the largest participation in the world cocoa market. It is the first cocoa exporter in Latin America and the fourth world exporter of Common Cacao and first in Fine Aroma Cacao. The importance of the farmers who are dedicated to this branch of economic activity is observed in the millions of dollars that this sector generates and the land areas that are used for the cultivation of cocoa. The objective of the article was: To analyze the socio-economic situation of small cocoa producers in the Guabito area, Mocache canton, Los Ríos province. A quantitative approach was used, which made it possible through a survey to generate a procedure that collects information from the participants personally without intervening in the scene of the phenomenon. With the research, an action plan was proposed to improve the situation of small cocoa farmers.
Keywords: socio-economic analysis; cocoa production; small cocoa farmers; cocoa sector